HEAVY METAL POLLUTION OF AGRICULTURAL SOILS AND VEGETABLES OF BHAKTAPUR DISTRICT, NEPAL (Scientific World, 2015)
The aim of this study was carried out to assess heavy metals (Cu, Zn, Pb, Cd,) in soils as well as vegetables of respective place of the Bhakatpur District (Manohara, Nagadesh, Bode, Hanumanghat, Sipadol, Tathali and Gundu). The leafy vegetables under this study were Spinach, Cauliflower, Carrot, Cabbage and Broad leaf mustard. The results showed that the concentration of heavy metals in the plants and soils from the Bhakatpur was proportional in the order Zn> Cu>Pb> Cd. Spinach showed the extremely high accumulation tendency towards the heavy metals compare to other vegetables. The geo-accumulation class (Igeo) indicates that the agricultural soil of Hanumanghat, Manohara, Nagadesh and Bode are moderately contaminated of Cd.Scientific World, Vol. 12, No. 12, September 2014, page 48-55